SUFFERING AS A PROCESS OF PURIFYING FAITH IN GOD (COMMENTARY ON THE BOOK OF JOB 2:1-10) - Ton, Sekundus Septo Pigang (Jurnal Matetes STT Ebenhaezer, 2023)
Writing this article focuses on suffering as a process of purifying faith in God, analyzing the interpretation of the Book of Job (2:1-10). Human life is never free from suffering. Suffering becomes an instrument accompanying the journey of human pilgrimage. In experiencing suffering, humans often ask whether God is being unfair. Where is God when humans suffer? These questions arrive at thoughts that provide arguments that God does not exist so that humans continue to suffer. This research aims to invite every human being to understand and interpret suffering as a purification process of faith in God. The method used in this research is interpretation analysis. The findings in this study are that through suffering Faith in God is increasingly purified. The all-loving and merciful God never allows humans to perish. And it is proven that He never allowed Satan to take Job's life.